Impact of Job Design on Employee’s Satisfaction Level in Pakistan - Hussain, Muhammad Ali; Ghouri, Muhammad Waleed Ayub; Hassan, Muhammad; Kanwal, Tehmina; Rashid, Mamoon (Advances in Social Sciences Research Journal, 2018)
Employee’s satisfaction in service organization was one of the major concern of every employer to enhance the growth of the organization. This research has analyzed the perspective of different employees of public and private universities. The study examined the behavior of employee’s who were asked to fill the questionnaire. This research was exploratory in nature and the measurement tool used for this study is quantitative. The Likert and dichotomous scale were used in questionnaire format. Data has been collected through properly administered questionnaire. Total respondents were 100. The research findings show that the independent variables motivation, feedback, job design, and healthy environment etc. have significant impact on the employee’s satisfaction. This research has an impact on all the small and medium scale organizations. There were some limitations due to shortage of time and funds. That’s why large geographical area hasn’t been covered. Through this research the employees feel more comfortable in the organization and committed towards the betterment of the organization. Key words: Job design, Employee’s satisfaction, motivation and feedback etc.